ANALISIS PENGARUH ASET COLLATERAL, FREE CASH FLOW, INVESMENT OPPOTUNITY, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nurul Zulficha; Irham Fahmi (Departemen Manajemen, 2021)
This study aims to examine the effect of collateral assets, free cash flow, investment opportunities, and profitability on the dividend policy of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX). The data used is panel data with a sample of 31 manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The analytical method used is panel data regression analysis with a fixed effect model. The results partially reveal that collateralized assets have no effect on policy dividends, free cash flow has a significant positive effect on policy dividends, investment opportunities have no effect on policy dividends, and profitability has a significant negative effect on policy dividends.